P44 Is restoration of pituitary function a realistic goal in endoscopic pituitary surgery?. Issue 3 (14th February 2019) - Galloway, L; Hayhurst, C
Abstract : Objectives: The ability to restore pituitary function after endoscopic transsphenoidal surgery (ETSS) in pituitary tumours causing hypopituitarism remains unclear. This study analyses patients that required steroid replacement therapy prior to ETSS, and reviews endocrine function postoperatively. Methods: A prospectively held pituitary database was retrospectively analysed from May 2011 – July 2017 at a tertiary university hospital. Patients requiring steroids for hypopituitarism pre-operatively were included. Patient demographic data, tumour characteristics, and tumour hormonal profile were recorded. Results: From a database of 156 patients, 28 (18%) were hypoadrenal pre-operatively and were included in the study. All patients underwent ETSS by a single neurosurgeon. The median age of patients was 56 years (range 17–81), whilst median follow-up was 48 months (range 6–78). 20 male patients and 8 female patients were included. All patients were established on steroid therapy preoperatively with either hydrocortisone (26 patients) or prednisolone (2 patients). 5 (18%) patients were able to stop steroid replacement postoperatively. The median time to cessation of steroid therapy was 4 months (range 2–16 months). Conclusions: Restoration of pituitary function following ETSS surgery was only successful in a small number of patients despite meticulous gland preservation. Our results suggest that restoration of function in all patients undergoing ETSS is an unrealistic goal and patients should be counselled accordingly.